Toward achieving sustainable food consumption: Insights from the life course paradigm - George P. Moschis (2020)
© 2020 by the authors. Trends in world population growth have created an agri-food demand that is unsustainable under the present resource-intensive agricultural systems and expected growth in income levels in many developing countries. As such, research and policy making related to sustainable development have focused on consumption. One major approach to sustainable consumption lies in shaping food demand that would require changes in people's present food consumption habits that are excessive and unhealthy, leading to overweight and obesity. In order to change food consumption habits, one must understand the factors that lead to their onset and change. This article offers the life course paradigm, which is increasingly used by social and behavioral scientists to study the development and change of various forms of behavior, as a research framework for studying the onset and change in food consumption habits. It shows how the life course approach could help guide future research not only on sustainable consumption, but also on environmental and social sustainability.